ISLAM DAN LINGKUNGAN (Model Pendidikan Islam Dalam Pembentukan Perilaku Peduli Lingkungan di SMA Negeri 6 Kendari) - Jumarddin La Fua,Samsul, Husain Insawan Ratna Umi Nurlila2 (IAIN Kendari, 2016)
This research examines the model of Islamic education in the formation of environmental care behavior in SMA Negeri 6 Kendari. The purpose of this research is to understand the introduction and understanding of environmental education as well as the form and behavior of matter formation environment in SMA Negeri 6 Kendari. The method of this research is qualitative research approach to the study of the field or field research, where researchers conduct research directly on site to get and collect data to be able to give you an idea of the reality on the ground in a systematic and describes the relationship of all the data obtained in particular relating to the establishment of environmental care behavior in SMA Negeri 6 Kendari. The object of this research is the principal, vice principal, teacher of Islamic education, Teachers Adiwiyata and Sman 6 Kendari. Data collection techniques in the study done by direct observation, interviews, and documentation. Data analysis in this research by reduction of data, data presentation and data verification. The results showed that the formation of environmental values matter in SMA Negeri 6 Kendari has done to build the character of the care for the environment through conditioning activities interact with the environment in discerning and wise. The process of cultivation of the value of environmental care in SMA Negeri 6 Kendari take a long time and done continuously and sustainably so that learners can receive values that have been instilled in him and will bring up the behavior of matter to the environment. The shape of the planting environment values which has been done by the SMA Negeri 6 Kendari through several patterns such as socialization, structuring the environment school vision being performed on every Tuesday, Thursday and Saturday, a text message or writing words of motivation that is framed in religus, and awarding examples example by all the citizens of the school in building a caring environment on behavior of SMA Negeri 6 Kendari.